Peran Kompetensi Sumber Daya Manusia Guna Meningkatkan Kualitas Laporan Keuangan - Aidilla Winda Prastika; Sri Trisnaningsih (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The reason for this study is to analyze all the more profoundly the job of human asset skill in working on the nature of monetary reports. The methodology strategy in this study utilizes a writing survey approach. The assets utilized in this study were acquired through auxiliary information using 20 articles relevant to this topic. Search articles through the Google Scholar database and selected based on the models utilized. The aftereffects of this study show that the ability of HR impacts working on the nature of monetary reports. The existence of good quality financial reports is also considered to work with clients of budget summaries during the time spent pursuing financial choices. With able assets during the time spent overseeing and introducing budget summaries, monetary reports will be more precise, successful, and effective. These results are expected to be helpful as material for consideration of an entity or institution to improve the competence of human resources in order to present quality financial reports. Keywords: competence, human resources, quality of financial reports